(untitled) (Al-Qamar, 2020)
Number of Qur’ānic verses contain the accounts of the virtues of prophet Muhammad(ﷺ). While reading these verses, commentators of the Quran highlight Muhammad’s specific rank among prophets; his holiness and his status in the hearts and eyes of the Muslims. This article studies in this regard the efforts of Fakhr al-Dīn al-Razī (d. 606AH) in his remarkable tafsīr al-Kabīr (also known as Mafātīh al-Ghaib), while interpreting the shortest Qur’ānic chapter Sūrah al-Kawthar. It finds that al-Rāzī in his commentary on referred Sūrah, presenting the traditional and rational arguments, has described the virtues of the Prophet in great detail and with inordinate respect. He proves that Allah Almighty has raised the rank of Prophet Muhammad (ﷺ) over all his other prophets.